Mental health literacy, mental health experiences and help-seeking behaviours of Chinese elite athletes: a qualitative study - Bu, Danran; Zhang, Chun-Qing; Liu, Jing-Dong; Han, Zhe; Wang, Xiang; Huang, Zhijian (Frontiers in Public Health, 2024)
Introduction Elite athletes' help-seeking on mental health might be influenced by their mental health literacy (MHL) and mental health experiences. The current study aimed to explore the MHL, experiences and help-seeking behaviours among elite athletes using a qualitative approach. Methods Face-to-face semi-structured interviews were conducted among 20 Chinese elite athletes, 12 coaches, and 5 team officials. Interview data was analyzed using content analysis. Results Seven main themes emerged from the analysis. The current study revealed that Chinese elite athletes suffered from various mental health issues and athletes' MHL levels, help-seeking attitudes and intentions, Chinese sports environments, and Chinese cultural background could impact their help-seeking behaviours. Conclusion Support for Chinese elite athletes' mental health and help-seeking requires improvement.